Pemberdayaan Masyarakat Lokal melalui Pengetahuan Tradisional dan Kesehatan Masyarakat di Era Pembangunan Sosial - Alex R I Ompusunggu (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This article explores community empowerment through the integration of traditional knowledge and public health in the context of contemporary social development. Employing a systematic literature review method, the study synthesizes and analyzes primary and secondary sources, including academic journals, government reports, ethnographic documents, and international publications from 2016-2026, focusing on cases in Indonesia and Southeast Asia. Key findings reveal that traditional knowledge such as jamu herbal remedies, tradition-based sanitation, and communal work practices strengthens public health programs by enhancing accessibility, cultural acceptance, and community resilience against modern challenges like pandemics and environmental degradation. However, barriers such as lack of scientific validation, urbanization, and centralistic policies often impede integration. The article proposes a hybrid framework combining evidence-based practice with local wisdom, including recommendations for capacity building, digital documentation, and inclusive policies. This approach not only supports sustainable empowerment but also contributes to the Sustainable Development Goals (SDGs), particularly SDG 3 and SDG 11, positioning local communities as primary agents of change in the social development era.